2013
DOI: 10.1086/674309
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low‐Density Lipoprotein Alters the Effect of Matrix Stiffness on the Formation of Endothelial Networks and Capillary Lumens

Abstract: Formation of new blood vessels is essential for vascular repair and remodeling, and it is known that biomechanical properties of extracellular matrix play a major role in this process. Our earlier studies have also shown that exposing endothelial cells to oxidized modification of low-density lipoproteins (oxLDL) increases endothelial stiffness and facilitates their ability to form cellular networks, suggesting that it facilitates endothelial angiogenic potential. The goal of this study, therefore, was to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…Earlier studies suggested that oxLDL inhibits endothelial proliferation (14), migration (15), and in vitro tube formation (16), as well as angiogenesis in the hind limb ischemia model (17). Our studies, however, showed that oxLDL may have a positive effect on the formation of endothelial networks in a 3D in vitro model of angiogenesis (3,18). Consistent with these findings, a similar effect was shown in a 2D system (19).…”
Section: Lipid Extraction and Lc-ms/ms Analysis Of Oxysterolssupporting
confidence: 90%
“…Earlier studies suggested that oxLDL inhibits endothelial proliferation (14), migration (15), and in vitro tube formation (16), as well as angiogenesis in the hind limb ischemia model (17). Our studies, however, showed that oxLDL may have a positive effect on the formation of endothelial networks in a 3D in vitro model of angiogenesis (3,18). Consistent with these findings, a similar effect was shown in a 2D system (19).…”
Section: Lipid Extraction and Lc-ms/ms Analysis Of Oxysterolssupporting
confidence: 90%
“…Our studies demonstrated that oxLDL also has a major impact on endothelial biomechanical properties, resulting in increased en-dothelial stiffness and contractility (9,54). Furthermore, we showed that this effect is accompanied by enhanced formation of endothelial networks and capillary lumens in threedimensional cell cultures (9,19,54). Recently, we showed that preexposure to oxLDL facilitates formation of functional capillaries in matrigels in vivo via activation of the RhoA/Rho kinase (ROCK) signaling pathway (45).…”
Section: Oxidized Modifications Of Low-density Lipoproteins; Rho Kinasementioning
confidence: 75%
“…Eighty to 90 percent confluent cells were transfected in Opti-MEM (Thermo Fisher Scientific) media using Lipofectamine 3000 Reagent (Invitrogen) and a siRNA mix for 4 h. HAEC-enriched cell culture media (Lonza) was then used to replace the Opti-MEM solution, and cells were allowed to grow for 48 h before experiments were performed. GFP-tagged-RhoGDI-1 was generated by PCR amplification (PFU; Stratagene) of the cDNA clone pOTB7-GDI-1 into p-EGFP-C3 vector using specific primer pairs [p-EGFP-FL-GDI-1 (AA1-204)] as described (19): forward primer 5=-AGGAATTCGAATGGCTGAG-CAGGAGCCCAC-3= and reverse primer 5=-CGGGATCCTCAT-CAGTCCTTCCAGTCCTTC-3=. We used a mutant containing the p115-RGS domain (RGS mutant) to address the role of p115RhoGEF in regulating RhoA activity as described (24) LDL isolation and oxidation.…”
Section: Cell Culture and Reagents Human Aortic Endothelial Cells (Hmentioning
confidence: 99%
“…More specifically, an increase in endothelial stiffness was shown to impair generation of nitric oxide in response to shear stress forces generated by blood flow (85), but also to facilitate flow-induced realignment of endothelial cells, a hallmark of their sensitivity to flow (77) and enhance transmigration of neutrophils through the endothelial layer (76). A series of studies also implicate endothelial stiffness as an important factor in angiogenesis (49,73,86,87). Furthermore, an increase in smooth muscle stiffness has been proposed to underlie the stiffening of blood vessels in hypertension and aging (88,89).…”
Section: Concluding Remarks and Implications For Cellular Functionmentioning
confidence: 99%